Characterisation of Pseudomonas coleopterorum, a new pathogen causing bacterial leaf spot on common cocklebur (Xanthium strumarium) in Iran - Heydari Rashnoo, Fatemeh; Sharifi, Rouhallah; Moarrefzadeh, Nahid; Marefat, Alireza; Hosseini, Saman (Biocontrol science and technology, 2025)
Weeds are known as the most important pests of crops. The use of biological methods for weed control has numerous advantages, such as its ability to positively affect ecosystems and human health through the reduction of harmful herbicide residues in soil, water, and crops. After the occurrence of leaf spot symptoms in common cocklebur (Xanthium strumarium L.) weed in northwestern Iran, the bacterial agents were isolated to obtain species with bioherbicide potential. Based on phenotypic and biochemical characteristics, as well as 16SrRNA and RNA polymerase subunit D (rpoD) genes sequencing, the causative bacteria were identified as Pseudomonas coleopterorum. The aggressive isolates (9N and 6N) were able to cause severe leaf-spotting lesions and tissue necrosis in common cocklebur, but they were not able to cause symptoms in the main crops in the region. To the best of our knowledge, this is the first report of leaf spot disease and the bioherbicidal potential of P. coleopterorum against common cocklebur in the world. In conclusion, these bacterial strains have the potential to be used in the integrated management of common cocklebur. However, before the potential of these bacterial strains as commercial bioherbicides could be realised, research into their field efficacy and environmental safety is necessary.